Effects of Elevation Gradient on Soil Carbon and Nitrogen in a Typical Karst Region of Chongqing, Southwest China. Issue 6 (14th June 2022) - Zhu, Guangyu; Zhou, Lihua; He, Xianjin; Wei, Pei; Lin, Dunmei; Qian, Shenhua; Zhao, Liang; Luo, Min; Yin, Xinhan; Zeng, Lian; Long, Yuxiao; Hu, Siwei; et al.
Abstract: Elevation changes create gradients in abiotic factors, which in turn affect soil erosion and carbon cycling. However, how elevation changes control soil ecological processes through temperature and the mechanism that affects the carbon cycle remain unclear. Therefore, we have studied the distribution of temperature, bulk density (BD), soil pH, mean weight diameter (MWD), clay, and diversity of soil fungal community diversity, and discussed the critical factors affecting soil organic carbon (SOC) and nitrogen (N) in a typical karst mountainous area. The results showed that the dominant phyla were Ascomycota (42.28%), Mortierellomycota (20.6%), Basidiomycota (17.83%), and Rozellomycota (11.82%). The elevation distributions of MWD, fungal diversity, the rate of SOC and N stocks change per temperature index, and SOC and N stocks all exhibited unimodal patterns. Additionally, temperature, fungal diversity, MWD, BD, and clay were the dominant factors explaining the variability of SOC and N, and SOC and N had a positive relationship with pH, BD, MWD, clay‐silt content, warmth index, and Sobs and Shannon diversity. Analyses showed that the warmth index regulated soil aggregates through fungal diversity and combined with BD to affect carbon sequestration, which was controlled by clay, the C:N ratio, and pH during the process. These conclusions have important implications for improving the SOC sequestration capacity in karst mountainous areas. Plain Language Summary: Climate change leads to the melting of glaciers and the rise of sea levels, which has a great impact on the land and various ecological services that humans depend on. The altitude gradient is an ideal area for studying response of C cycle to climate change due to the dramatic changes in many environmental factors such as temperature. This study found that mid‐elevation is the most significant climate change gradient that affected soil organic carbon in karst mountains of southwest China, which is mainly controlled by temperature, soil structure, and fungal diversity. The composition of fungal communities is consistent with the distribution of arid farmlands at global scale, and is closely related to the soil nutrients and stress tolerance and competitive abilities of the fungal. Temperature can affect soil structure by regulating fungal communities, and this process is mainly affected by clay, C:N ratio, and pH. As nitrogen deposition aggravates the imbalance of soil acidity and C:N ratio, it exacerbates the impact of climate change on C sequestration and soil structure. Therefore, we hope to further explore the coupling mechanism of C, nitrogen and erosion, hoping to provide a theoretical basis for increasing C sinks and preventing rocky desertification. Key Points: Mid‐elevation is the key research object of carbon and nitrogen cycle and the soil ecological process in karst mountainous areas Temperature, fungal diversity, soil aggregates, bulk density, pH, and clay content were dominant factors that explain the variability of soil organic carbon Temperature regulates soil aggregates through fungal diversity and combines with bulk density to affect carbon sequestration